HEALTHCARE WORKERS X COVID-19 AND POPULATION-WIDE USE OF FACE MASKS TO PREVENT SARS-COV-2 TRANSMISSION AND INFECTION - Passos, Kauany; Santos, Matheus Peres dos; Campiolo, Edmara Laura (InterAmerican Journal of Medicine and Health, 2020)
Background: due to the overload of health services because of the outbreak of COVID-19 pandemic, the use of disposable personal protective equipment (PPE) by the population has been discouraged by several public agencies, in order to earmark these items to healthcare workers because of their large exposition in frontline attendance of infected patients by the disease causing virus, SARS-CoV-2. The current recommendation is to prefer the non-professional materials made PPE, specially facemasks, for the community members. Objectives: through automatic searches in international databases and manual searches in several agencies and periodicals throughout the world, we seek to describe the significance of PPE in healthcare workers protection against SARS-CoV-2; we also intend to determine non-professional materials effectiveness in block the community transmission and infection of the virus and to recognize the viability of widespread use of these devices. Conclusion: a shortage of PPE for health professionals promotes the need to delivery this few equipment for those who keep the health system operating, as well as create cloth face masks' idea as an alternative for the population in general. There are some evidence, with variable statistical significance, to support the widespread use of masks by the population, even thought its effectiveness is reduced to aerosols transmitted agents. It is preferred, according to the obtained results, the use of disposable materials, TNT made and with filter elements or N95/FPP2 masks, as a public measure, however, in the absence or difficult to acquire these equipment, as in contingency situations, it’s possible to use cotton tissues, cotton mix tissues (55% polyester and 45% cotton), tricoline and others.